The Influence of Media Exposure, Company Size, and Profitability on Carbon Emission Disclosure in Basic Materials Companies in Indonesia - Harahap, Bela Fadhilah; Ansori, Muslim; Mochtoha, Himawan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The acceleration of global warming caused by carbon emissions continues to be a pressing worldwide concern. Disclosing carbon emissions is a measure companies can adopt to tackle environmental and social issues. In Indonesia, the extent of carbon emission disclosure remains comparatively modest, as it is conducted primarily on an initiative basis. This research primarily aims to ascertain the partial impact of media exposure, company size, and profitability on carbon emission disclosure. The research sample was obtained through purposive sampling, comprising 63 samples from basic materials businesses listed on the Indonesia Stock Exchange for the period of 2021-2023. The multi-linear regression model of analysis used in this research was performed in SPSS 20 using the SPSS 20 measurement tool. The research indicates that media exposure, organizational scale, and profitability influence carbon emission disclosure.